Delineation of molecular changes in intrahepatic cholesterol metabolism resulting from diminished cholesterol absorption - Joyce J. Repa; Stephen D. Turley; Gang Quan; John M. Dietschy (Journal of Lipid Research, 2005)
The absorption of cholesterol by the small intestine is a major route for the net entry of cholesterol into the body and can therefore affect the plasma low density lipoprotein-cholesterol (LDL-C) concentration. These studies used ezetimibe, a potent inhibitor of cholesterol absorption, to delineate the biochemical and molecular changes in intrahepatic metabolism and biliary lipid secretion when there is a major reduction in chylomicron cholesterol delivery to the liver. In female LDL receptor (LDLR)-deficient (LDLR−/−) mice fed a basal diet containing ezetimibe (0–10 mg/day/kg body weight), cholesterol absorption was reduced up to 91%, fecal neutral sterol excretion was increased up to 4.7-fold, and plasma total cholesterol concentrations decreased by up to 18%. Blocking cholesterol absorption prevented the accumulation of very low density lipoproteins and LDL in the circulation of LDLR−/− mice fed a lipid-rich diet. In female LDLR+/+ mice fed the lipid-rich diet with ezetimibe, the relative mRNA level for the LDLR in the liver was 2-fold greater than in matching mice given the lipid-rich diet alone.We conclude that in the mouse the reduction in plasma LDL-C levels induced by blocking cholesterol absorption reflects both a diminished rate of LDL-C production and a modest increase in hepatic LDLR expression.